Huth & Co.'s credit strategies: A global merchant-banker's risk management, c. 1810-1850 - Manuel Llorca-Ja\~na (Estudios de Economía, 2015)
The pivotal role played by non-banking institutions in supporting the expansion of international trade after the Napoleonic Wars and before first globalization c. 1870 - 1913 has long been recognised. Merchant-bankers in particular played a crucial role by advancing monies to consignors of products all over the world. Without this form of credit, many international trade operations could not have taken place. Despite the important extant literature on merchant-banking, we knew little about how these international lenders protected themselves against the risks involved in advancing during this period, in particular for merchantbankers who had diversified both geographically and by products. This paper is concerned with the risk protection strategies followed by one of these actors: Huth & Co., the first of these companies to globalize their operations. During this expansionary period they provided credit to many of their connections all over the world, thus becoming an important financial intermediary within world trade. This paper, therefore, provides the first account of the credit risk management strategies followed by this pioneer global lender.
Keywords: N23; N73; N83; 330; merchant-banking; risk management; nineteenth century; Great Britain; globalization